2017
DOI: 10.1177/0959680117694272
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public services outsourcing on work and employment conditions in different national regimes

Abstract: This article examines the impact of outsourcing of public services on employment relations and working conditions in three countries: Italy, the UK and Denmark. It presents six matched case studies and investigates whether contracting out by public administrations causes a market-driven convergence across national boundaries or whether cross-country differences endure. Though outsourcing blurs the organizational boundaries between public and private sectors everywhere, making terms and conditions of employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Outsourcing: Outsourcing means assigning one part or part of a firm's internal activities to natural or juridical persons outside the firm in the form of a contract or agreement (Mori, 2017). In its preliminary concept, outsourcing means that employees outsource one part of the firm's activities, and indeed, they exit the process, which is performed by employees who supply the activities (Skipworth, Delbufalo, & Mena, 2020).…”
Section: Theoretical Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Outsourcing: Outsourcing means assigning one part or part of a firm's internal activities to natural or juridical persons outside the firm in the form of a contract or agreement (Mori, 2017). In its preliminary concept, outsourcing means that employees outsource one part of the firm's activities, and indeed, they exit the process, which is performed by employees who supply the activities (Skipworth, Delbufalo, & Mena, 2020).…”
Section: Theoretical Principlesmentioning
confidence: 99%
“…Performance does not have a unit, and a certain definition and a more suitable definition can be employed for its use. Various definitions have been proposed about performance utilized in humanities literature, especially management and other phrases like human performance, job performance, and organizational performance (Mori, 2017). Performance is a behaviour to achieve organizational and measured or evaluated purposes, and it is a general construct that emphasizes how organizational operations are performed.…”
Section: Theoretical Principlesmentioning
confidence: 99%
“…The most evident relates to differences in pay and working conditions, which might be caused by the presence of different standards set in collective agreements covering the public and the private sectors or by different levels of collective bargaining coverage in public and private organisations (Jaehrling, 2015). Moreover, gaps in employment conditions might be influenced by general institutional rules regulating the labour market, like the application of minimum wage regulations or similar wage floors (Gautié and Schmitt, 2010), as well as by rules defining the terms of employment of transferred workers, like those set in the Transfer of Undertakings Directive (TUPE) (Mori, 2017) or in other types of provisions imposing employment standards to service providers (Wright and Brown, 2013). Secondly, public/private gaps might be related to the relevance of collective institutions as defined by trade union density levels and their capacity to influence employment conditions in public and private organisations (Grimshaw et al, 2015).…”
Section: The Missing Linkage Between the Different Determinants Of Oumentioning
confidence: 99%
“…Differences in union strength and employees' voice capacity across the public/private divide might be another incentive to outsource. Finally, incentives to outsourcing may be related to legal differences in public employment status compared to the private one (Bach and Bordogna, 2011), and to associated differences in employment protection, career security and other prerogatives (Mori, 2017). Accordingly, public employers might decide to rely on external contractors for shifting workers' employment status from public to private law, thereby acquiring greater flexibility in the management of the employment relationship, even if employment conditions or industrial relations characteristics do not differ substantially.…”
Section: The Missing Linkage Between the Different Determinants Of Oumentioning
confidence: 99%
“…Within the business and management literature, there are a number of examples of the new dynamics created as a result of outsourcing (e.g. Baraldi, Proença, Proença, & de Castro, 2014;Mori, 2017). While academics in HPE have begun to question these new dynamics, through the data generated in this study I have demonstrated the blurring of boundaries both in relation to curriculum development and the HPE teaching profession.…”
Section: Blurring Boundariesmentioning
confidence: 81%